Digitalisasi Al-Qur'an dan Tafsir Sosial Media di Indonesia - Muhamad Fajar Mubarok; Muhamad Fanji Romdhoni (UIN Sunan Gunung Djati Bandung, 2021)
Al-Qur'an and Tafsir in the digital era are closely related to current technological developments. Various information and data that used to be difficult to obtain, with the development of technology become very easy, including the Al-Qur'an and its interpretation. From the editorial, the author focuses this discussion on the question,